SOCIAL CONTENT OF ADMINISTRATIVE RESPONSIBILITY - Hryshyna, Natalia; Rostovska, Karyna (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2022)
Liability in law is a multifaceted category that is used by various industries and is of great importance to law enforcement. Interest in this category is due to the importance of legal responsibility for the proper functioning of law and ensuring effective law and order. At present, the institution of responsibility as a social phenomenon needs deep understanding, legal interpretation and regulatory improvement. Social responsibility is considered as a reflection of the objectively existing need to regulate the actions of all individuals in the course of their activities. Legal responsibility in all the richness of its specificity of a socially working construction has not lost the general qualities of the institution of social control, moreover, the action of its mechanism does not go beyond the regularities of the social mechanism of responsibility as a whole.